Poems - Longfellow, Henry Wadsworth 1807-1882.; Fuller, Edmund 1914-2001 (New York : Dent., 1947)
A selection of "the best and most characteristic" poetry of the nineteenth-century American poet.
Keywords: Children's poetry, American; Poetry